Adaguc-Server: Interactive Access to Heterogeneous Meteorological and Climatological Datasets Using Open Standards. (9th December 2021) - Plieger, Maarten; de Vreede, Ernst
Adaguc-server is an open source geographical information system to visualize, combine, compare and share real-time meteorological, climatological and remote sensing data via OGC standards. During implementation of the server, we ran into the limits of what is possible with OGC standards. To overcome the found limits, extensions to the OGC standards were developed to achieve the required functionality and interoperability. The presented solution is used as a building block in a web based meteorological working station.